2011
DOI: 10.3174/ajnr.a2539
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Diffusion-Weighted Imaging of Neck Lymph Nodes Using 2D-Single-Shot Interleaved Multiple Inner Volume Imaging Diffusion-Weighted Echo-Planar Imaging at 3T

Abstract: BACKGROUND AND PURPOSE: 2D-ss-IMIV-DWEPI is an ss-DWEPI with greatly reduced geometric distortion. The purposes of this paper are to 1) evaluate of the utility of 2D-ss-IMIV-DWEPI for high-resolution neck LN imaging; 2) determine whether 2D-ss-IMIV-DWEPI can depict normal LN hilum; and 3) evaluate whether the inclusion of LN hilum within ROIs affects the measured LN ADC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In case of neck lymph node measurements surrounding perilymphatic tissue as, for example, muscles or salivary gland tissue as well as hilar vascular structures could be incorporated in the ROI if the lymph node is of small size. The contribution of these falsified voxels to the measurement influences the analysis of ADC values to an unknown variable extent (26).…”
Section: Discussionmentioning
confidence: 99%
“…In case of neck lymph node measurements surrounding perilymphatic tissue as, for example, muscles or salivary gland tissue as well as hilar vascular structures could be incorporated in the ROI if the lymph node is of small size. The contribution of these falsified voxels to the measurement influences the analysis of ADC values to an unknown variable extent (26).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic accuracy of DWI can be affected substantially by imaging resolution. Park et al [35] developed a high-resolution DWI method allowing 1-mm 2 in-plane resolution and 2-mm slice thickness, albeit with a smaller FOV, with which they successfully identified the hilar structure of cervical lymph nodes. With this kind of technical development, DWI promises to be a promising tool to detect clinically occult metastatic lymph nodes.…”
Section: Detection Of Metastatic Lymph Nodesmentioning
confidence: 99%
“…Then, lower ADC values than expected will be obtained, giving a false positive; as the presence of a preserved fatty hilum is a morphological criterion of benignity. However, other studies have shown significantly differences when the fatty hilum is included, as it would induce an overestimation of real ADC value of lymph nodes [21]. Nevertheless is clear that hilum should be excluded when a ROI is placed for ADC measurement of lymph nodes.…”
Section: Physical Basis Of Dwi and Technical Aspects Of Dwi In Thementioning
confidence: 99%